Modeling consent in the time of COVID-19. Issue 1 (8th May 2020) - Knoppers, Bartha Maria; Beauvais, Michael J S; Joly, Yann; Zawati, Ma'n H; Rousseau, Simon; Chassé, Michaël; Mooser, Vincent
Abstract: Effective responses to the COVID-19 pandemic require novel solutions for research and responsible data sharing. Biobanking presents itself as a key priority in furthering our understanding of COVID-19. In this article, we propose a tripartite approach to consent to create resources for research relating to COVID-19. The approach aims to link three levels of participation: COVID-19 patients, respiratory/infectious disease patients, and longitudinal study participants. We explore the potential approaches that can be taken to consent processes with these three participant groups. We furthermore describe an access model for both single-site and multi-site data and sample storage. Through dealing with these topics at a high level, the model may be adapted to local legal and ethical requirements while still pursuing its ultimate goal: the creation of a research infrastructure that supports transparent, strong, and open science.